Enhancing Charge Transport of 2D Perovskite Passivation Agent for Wide‐Bandgap Perovskite Solar Cells Beyond 21%. Issue 6 (8th June 2020) - Ye, Jiselle Y.; Tong, Jinhui; Hu, Jun; Xiao, Chuanxiao; Lu, Haipeng; Dunfield, Sean P.; Kim, Dong Hoe; Chen, Xihan; Larson, Bryon W.; Hao, Ji; Wang, Kang; Zhao, Qian; et al.
Abstract : Passivation Agents In article number 2000082, Fei Zhang, Kai Zhu, and co‐workers design a more efficient and stable perovskite solar cell by partially replacing phenylethylammonium (PEA + ) with pentauorophenethylammonium (F5PEA + ) as the 2D perovskite passivation agent by forming a strong noncovalent interaction between the two bulky cations, which enhances charge transport, and presents the highest performance for reported wide‐bandgap perovskite solar cells.